Comparison of mental health in individuals with primary ciliary dyskinesia, cystic fibrosis, and parent caregivers. (February 2023) - Graziano, Sonia; Ullmann, Nicola; Rusciano, Raffaela; Allegorico, Annalisa; Boldrini, Francesca; Rosito, Lorenza; Quittner, Alexandra L.; Cutrera, Renato; Tabarini, Paola
Abstract: Introduction: Individuals with chronic respiratory diseases and caregivers are at higher risk for depression and anxiety. Primary ciliary dyskinesia (PCD) and cystic fibrosis (CF) are both rare genetic diseases, characterized by recurrent respiratory infections. This study compared depression and anxiety in people with PCD (pwPCD) and CF (pwCF), and caregivers, using the screening tools recommended in the CF guidelines. Methods: Patient Health Questionnaire (PHQ-9) and Generalized Anxiety Disorder (GAD-7) were administered to a PCD and CF sample. Given that PCD is extremely rare, they were matched on age and sex to pwCF at a 1:2 ratio. Similar procedures were performed with parents. Results: A total of 63 patients and 129 caregivers participated: 21 pwPCD and 42 pwCF (ages 12–34 years) plus 43 caregivers of pwPCD and 86 caregivers of pwCF. A high percentage of patients scored above the cut-off for depression (PCD: 33%; CF: 43%) and anxiety (PCD and CF both: 43%), mostly mild. Similarly, a high percentage of caregivers scored above the cut-off for depression (PCD: 42–54%; CF: 45–46%) and anxiety (PCD: 47–54%; CF: 39–56%). Suicidal ideation was endorsed by 9.5% of pwPCD, 20% of mothers and 10% of fathers and 5% of pwCF, 3% of mothers, but no fathers. Conclusion: A large percentage of patients and caregivers reported elevated psychological distress and suicidal ideation. Addressing psychological symptoms is critical given they are associated with poor adherence, missed clinic visits, increased inflammation and worse quality of life. Mental health screening and treatment should be integrated into PCD care. Highlights: A high percentage of PCD and CF patients and caregivers were elevated on depression and anxiety. Suicidal ideation was endorsed more by patients and caregivers with PCD than CF. Mental health should be integrated into the care of people with PCD and their families.